Market Microstructure and Incentives to Invest - Spulber, Daniel F. (Journal of Political Economy, 2002)
Market organization significantly affects total output and incentives for firms to invest. I compare three types of market organization. In a market with search and random matching, total output is excessive and there are incentives for inefficient underinvestment. In a market with a monopoly dealer, total output is insufficient and underinvestment also occurs. Competition between the search market and the dealer market improves incentives to invest, and competition between dealers yields efficient total output and investment. This suggests that additional entry of wholesalers and other interbusiness dealers should stimulate aggregate business investment.